Determination of physical crossllink between carrageenan and glyoxylic acid using density functional theory calculations [Penentuan ikatan sambung silang fizikal antara karagenan dan asid glioksilik menggunakan pengiraan teori fungsi ketumpatan] - Siti Hana, Abu Bakar; Fatmawati, Adam (Malaysian Society of Analytical Sciences, 2017)
Film of carrageenan and glyoxylic acid has been produced with an aim for hard capsule application through manipulation of physical crosslink. In this paper, the computational calculation has been used through utilization of density functional theory to predict the possible location of the physical crosslink in the conjugate complex between carrageenan and glyoxylic acid (film of carrageenan and glyoxylic acid). The calculations for pure kappa carrageenan (k-carrageenan), glyoxylic acid and conjugate complex were carried out using Gaussian 09W; and analysis of molecular electrostatic potential (MESP) was carried out using Gaussview 5. The molecular electrostatic surface potential (MESP) for optimized structure for k-carrageenan and glyoxylic acid have been generated with the red region represents the most negative electrostatic potential which can be found around oxygen and sulphur atoms for the carrageenan molecule. While the blue region that represents the most positive electrostatic potential which can be found around the hydrogen atom far from the double bond oxygen atoms in glyoxylic acid. Therefore, both of this regions may interact and form physical crosslink via hydrogen bond interaction.